1994
DOI: 10.1093/protein/7.11.1373
|View full text |Cite
|
Sign up to set email alerts
|

Circularly permuted dihydrofolate reductase of E.coli has functional activity and a destabilized tertiary structure

Abstract: Three circularly permuted variants of Escherichia coli dihydrofolate reductase genes were constructed. Linkers coding tri- and pentapeptides were used to connect the natural 5'- and 3'-terminal ends. Only one variant of circularly permuted protein with tripeptide linker and the cleavage of the peptide bond between 107 and 108 amino acid residues was produced in a good yield. The expressed protein was insoluble in the cells, but at pH 8.0 and higher the isolated protein was soluble. Enzymatic assay and physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
30
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 0 publications
1
30
0
Order By: Relevance
“…Several other monomeric proteins have since been circularly permuted through genetic manipulations, all of which maintain a nativelike function. [3][4][5][6][7][8][9][10][11] Single subunits of multimeric proteins can also withstand circularly permuted sequences. For example, circularly permuted catalytic chains of aspartate transcarbamoylase combined in vitro with regulatory chains produced a folded and functional multimeric protein.…”
Section: Introductionmentioning
confidence: 99%
“…Several other monomeric proteins have since been circularly permuted through genetic manipulations, all of which maintain a nativelike function. [3][4][5][6][7][8][9][10][11] Single subunits of multimeric proteins can also withstand circularly permuted sequences. For example, circularly permuted catalytic chains of aspartate transcarbamoylase combined in vitro with regulatory chains produced a folded and functional multimeric protein.…”
Section: Introductionmentioning
confidence: 99%
“…However, circular permutation of E. coli as well as mDHFR has shown that its primary structure can be radically altered and yet yield active enzyme with native-like structure (16). We have designed two fragments of mDHFR consisting of the sequences coding for F [1,2], and for F [3], each of which is covalently linked to an interacting domain (GCN4 leucine zipper).…”
mentioning
confidence: 99%
“…The functioning residues on the peptide backbone are then arranged to give the proper configuration for effective catalytic activity. Because enzymes cleaved at certain sites have been demonstrated to show catalytic activity as high as that of uncleaved enzyme (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16), chain connectivity must not be absolutely required for catalytic activity. This means that chain connectivity is crucial for catalytic activity in some regions, but in others, it is not.…”
mentioning
confidence: 99%